Unlocking Consumer Behavior: The Interplay of Marketing Mix and Hygiene Perceptions in Kembar Water's Market Success - Astri Ayu Purwati; Eka Kurniawan; Teddy Chandra; Mazzlida Mat Deli; Muhammad Luthfi Hamzah; Siti Intan Nurdiana Wong Abdullah (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study aims to examine the impact of marketing mix strategy and hygienic perception on consumer trust and purchase decisions for Kembar Water, a bottled drinking water (AMDK) brand. The target population for this research includes consumers who have purchased Kembar Water products. From a total population of 380 consumers, a sample size of 100 respondents was determined using the Slovin formula. Random sampling was employed as the sampling technique. Data were collected through institutional documentation and online questionnaires distributed via Google Forms. The data analysis techniques included descriptive analysis and Structural Equation Modeling (SEM) using Smart PLS software. The findings of the study reveal that: (1) The marketing mix strategy variable does not significantly influence consumer trust. (2) The hygienic perception variable has a positive and significant impact on consumer trust. (3) The marketing mix strategy variable does not significantly affect consumer purchase decisions. (4) The hygienic perception variable positively and significantly influences consumer purchase decisions. (5) The consumer trust variable has a positive and significant effect on consumer purchase decisions.